Enhancing Genetic Diversity in Ornamental Chili Pepper Through Interspecific Crossing - Wirasti, Christina Astri; Purwantoro, Aziz; Murti, Rudi Hari; Purwestri, Yekti Asih (Comunicata Scientiae, 2025)
he observation of morpho-agronomic characteristics of ornamental chili pepper is essential to enhance diversity and get novel cultivars. Interspecific crossing is extremely effective in introducing a desirable character, resulting in a novel cultivar of agronomic relevance. This study aimed to identify the genetic diversity of crossing two open-pollinated ornamental chili pepper cultivars (‘Black Pearl’/Capsicum annuum & ‘Rawit Prentul’/Capsicum frutescens) as parents based on twenty morpho-agronomic characters (plant, flower, and fruit). The genetic diversity analysis in interspecific ornamental pepper offspring shows varying results from narrow to broad diversity. The broad genetic diversity in F1 Black Pearl x Rawit Prentul is found in replace with vegetative character, while the reciprocal cross (Rawit Prentul x Black Pearl) is seen in replace with vegetative and fruit characteristics. change The heatmap analysis identified the F1 into three major clusters while the dendogram analysis divided the F1 and F1 reciprocal into four major clusters. In F1 offsprings showed significantly negative and positive correlation between fruit color and morpho-agronomics character.